Divergent magnetic resonance imaging atrophy patterns in Alzheimer's disease and primary age‐related tauopathy. (20th December 2022) - Quintas‐Neves, Miguel; Teylan, Merilee A.; Morais‐Ribeiro, Rafaela; Almeida, Francisco; Mock, Charles; Kukull, Walter A.; Crary, John F.; Oliveira, Tiago Gil
Abstract: Background: Primary age‐related tauopathy (PART) is a pathological disorder characterized by the presence of tau‐positive neurofibrillary tangles (NFTs) and no amyloid‐beta (Aβ) deposition ("definite PART"). Currently, the diagnosis of PART is histologically assessed by the presence of tau positive NFT with Braak staging and a Consortium to Establish a Registry for Alzheimer's disease (CERAD) Aβ stage of 0. Method: Our study compared brain magnetic resonance imaging (MRI) with neuropathological findings in patients with PART and AD, while assessing the relationship between brain atrophy and clinical impairment. We analysed 233 participants: 32 with no plaques ("definite" PART ‐ CERAD 0), and 201 cases within the AD spectrum, with 25 with sparse (CERAD 1), 76 with moderate (CERAD 2) and 100 with severe (CERAD 3) degree of neuritic plaques. Result: Upon correcting for age, sex and age difference at MRI and death, there were significantly higher levels of atrophy in CERAD 3 compared to CERAD 1‐2 and a trend compared to CERAD 0. In the anterior temporal region, there was a trend for higher levels of atrophy in CERAD 0 compared to CERAD 1. We then assessed the correlation between regional brain atrophy and CDR‐sum‐of‐boxes score for PART and AD, and found that overall cognition deficits are directly correlated with regional atrophy in the AD continuum, but not in definite PART. We further observed correlation between regional brain atrophy with multiple neuropsychological metrics in AD, while PART showed only specific correlations between language deficits and anterior temporal atrophy. Conclusion: Overall, these findings support PART as an independent pathologic process from AD.